Factors affecting trust in Bangladesh police among urban male residents: a test on instrumental and expressive model - Hasan, Md Khalid; Rumi, Maruf Hasan; Ahsan, Abu Hossain Muhammad (Frontiers in Sociology, 2025)
ObjectivesThe primary aim of this study was to examine the level of trust male residents in urban areas of Bangladesh have in the police. Additionally, the study sought to explore the various factors that influence this trust.MethodThis study employed a robust cross-sectional research design. Utilizing multi-stage sampling techniques, the survey was conducted among male respondents (aged 18 or over) through in-person interviews, and the data was collected using the Kobo Toolbox. A total of 1,108 data were collected from four city corporation areas in Dhaka, Sylhet, Khulna, and Rangpur districts, ensuring a comprehensive representation of urban areas in Bangladesh.ResultsThe study revealed that male citizens in urban areas of Bangladesh have a moderate level of trust in the police. Trust in neighbors was found to be a significant and positive factor influencing trust in police. The study also found that neighborhood relative safety was positively associated with trust in police, while the perceived crime problem in the locality had a negative impact on trust in police. Furthermore, middle-aged (39–49 years old) and older men (over 50 years old) were found to have significantly lower trust in police than young adult (19–39 years old) respondents. Location was also a crucial factor, with respondents from Khulna City exhibiting substantially higher trust in the police than male residents of other cities.ConclusionThe study underscores the need for the law enforcement agency to address the current situation. To improve public trust in the police, it is crucial that the agency increases its social media presence and launches campaigns to highlight its recent successes.